2010
DOI: 10.2298/psi1003219v
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proficiency and age of language acquisition on working memory performance in bilinguals

Abstract: This study examined language proficiency and age of language acquisition influences on working memory performance in bilinguals. Bilingual subjects were administered reading span task in parallel versions for their first and second language. In Experiment 1, language proficiency effect was tested by examination of low and highly proficient second language speakers. In Experiment 2, age of language acquisition was examined by comparing the performance of proficient second language speakers who acquired second l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
2
20
1
Order By: Relevance
“…These findings also contribute to an increasing number of studies that report a bilingual advantage for verbal WM (e.g. Blom et al, 2014;Kaushaskaya et al, 2014;Vejnovic et al, 2010). The present results go beyond other studies in showing that the simultaneous bilinguals, the early successive bilinguals, and the late successive bilinguals also performed significantly better than the monolinguals on measures of verbal WM.…”
Section: Discussionsupporting
confidence: 78%
“…These findings also contribute to an increasing number of studies that report a bilingual advantage for verbal WM (e.g. Blom et al, 2014;Kaushaskaya et al, 2014;Vejnovic et al, 2010). The present results go beyond other studies in showing that the simultaneous bilinguals, the early successive bilinguals, and the late successive bilinguals also performed significantly better than the monolinguals on measures of verbal WM.…”
Section: Discussionsupporting
confidence: 78%
“…This leaves open the question of age of acquisition (AoA), which is also often confounded with proficiency, but which may uniquely influence the development of PWM because L2 learners are exposed to the L2 after the sensitive period for phonological development. Vejnović, Milin, and Zdravković (2010) examined whether AoA influenced verbal memory abilities in bilingual speakers by testing equally proficient groups of adult successive bilinguals who acquired their L2 at age 4 or age 9, on average. They found that, while both groups performed similarly on verbal memory tasks in their L1, the bilinguals who acquired their L2 earlier performed better on L2 verbal memory tasks than the group who acquired their L2 later.…”
Section: Impoverished and Enriched Language Inputmentioning
confidence: 99%
“…There is a substantial body of research on word recall in relation to WM and how WM processes simple and complex words. Further, many studies have been conducted on prefixed and suffixed words and how they are recalled in WM (Carroll, 2008;Cohen-Mimran, Adwan-Mansour, & Sapir, 2013;Marslen-Wilson & Tyler, 2007;McKinnon, Allen, & Osterhout, 2003;Rastle & Davis, 2008;Service & Maury 2014;Service & Tujulin, 2002;Taft & Forster, 1975;Veinovic, Milin, & Zdravcoic, 2010) . Further, in the past several decades, many studies have been conducted on the relationship between WM and L1 and L2.…”
Section: Working Memory Modelmentioning
confidence: 99%
“…In recent years, there have been a number of studies addressing whether or not a person who has learned the L1 and then the L2 employing the phonological loop system shows different WM capacity in the two languages. This research has also looked at what factors may possibly cause these differences (Veinovic et al, 2010). However, to the best knowledge of the researchers, no study has been conducted investigating word recall in Arabic and English and whether or not prefixed and suffixed verbs are recalled differently in both languages.…”
Section: Working Memory Modelmentioning
confidence: 99%
See 1 more Smart Citation